Continuing Health Education: the experience of social work with Family Health Teams - Santos, Eliezer Rodrigues; Lanza, Liria Maria Bettiol; Carvalho, Brígida Gimenez (Textos & Contextos (Porto Alegre), 2011)
Continuing Health Education provides for building collective knowledge within health services and has in Family Health Multidisciplinary Residency the potential for creating moments of reflection. Continuing education workshops were conducted with professionals from a Family Health Unit in the northern region of Londrina/Paraná, where a team of residents was working. This study structures thoughts on the role of social workers in these workshops, especially the discussions of a socio-political nature, in which the social worker was a facilitator. It was conducted using the participant research technique, lasted for ten months and the subjects were health workers at the above-mentioned unit. It can be concluded from the findings that socio-political reflections were not carried out with the necessary amplitude for these services and that social workers can contribute so that these can be affirmed as elements for changing the way health care is provided.